2011
DOI: 10.1007/s11071-011-9969-6
|View full text |Cite
|
Sign up to set email alerts
|

Soliton dynamics and interaction in the Bose–Einstein condensates with harmonic trapping potential and time-varying interatomic interaction

Abstract: Investigated in this paper is the quasi-onedimensional Gross-Pitaevskii equation, which describes the dynamics of the Bose-Einstein condensates with the harmonic trapping potential and timevarying interatomic interaction. Via the Horita method and symbolic computation, analytic bright N-soliton solution is obtained. One-, two-and three-soliton solutions are analyzed graphically. Based on the limit analysis on the one-and two-soliton solutions, the modulation on the speed of the matter-wave bright solitons is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The interference pattern becomes more prominent as we increase relative velocity. This interference pattern is due to the feedback of the wave properties of the soliton that take over at higher relative speeds [16][17][18]. Here these humps are nonlocally induced by coupling the two soliton solutions of reverse space-time nonlocal NLS equation at different but opposite sites.…”
Section: Two-soliton Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interference pattern becomes more prominent as we increase relative velocity. This interference pattern is due to the feedback of the wave properties of the soliton that take over at higher relative speeds [16][17][18]. Here these humps are nonlocally induced by coupling the two soliton solutions of reverse space-time nonlocal NLS equation at different but opposite sites.…”
Section: Two-soliton Solutionmentioning
confidence: 99%
“…But what is happening in the region where humps interact, is still debatable and will help us to explore many exciting features of nonlinear collisions. A few years back in 2016, Zhao et al studied nonlinear interference patterns associated with solitons asymptotically through density calculation and found that the pattern is contingent on relative velocities of the interacting solitons [16] (Also see [17,18]). Wave-like properties of soliton are intensively explored lately in the context of matter-wave in Bose-Einstein condensations [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics and stability of solitons have been investigated both theoretically and experimentally in BECs confined by magnetic traps (harmonic potentials) [8, 9], optical lattices (periodic potentials) [10] and double‐well potentials [11]. Recently, BECs trapped by the symmetrical Pöschl–Teller (PT) potential (hyperbolic potential) have been theoretically studied [12].…”
Section: Introductionmentioning
confidence: 99%